ACPA and bone loss in rheumatoid arthritis topical collection on rheumatoid arthritis - Kocijan, Roland; Harre, Ulrike; Schett, Georg (Current Rheumatology Reports, 2013)
Rheumatoid arthritis (RA) is an autoimmune inflammatory disease characterized by bone loss. Degree of inflammation and autoantibody positivity have both been identified as important initiators of skeletal damage in RA. Whereas it is well appreciated that inflammation initiates bone loss via the action of cytokines, the effect of autoantibodies in initiating bone destruction has long been underestimated. It has, nonetheless, been known for years that antibodies against citrullinated proteins (ACPA) and rheumatoid factor are associated with a more destructive disease course. It was recently shown that ACPA bind osteoclast precursor cells and directly promote their differentiation into bone-resorbing osteoclasts. Other results have shown that in ACPA-positive individuals bone loss starts even before the onset of clinical disease; this is indicative of the independent effect of these antibodies in initiating skeletal damage. The observation that the mere presence of ACPA is associated with pathological changes suggests that these antibodies have functional properties and initiate the onset of disease long before patients consult the rheumatologist because of symptomatic joint disease. These findings also indicate that "RA" is a syndrome rather than a single disease, suggesting that autoantibody-positive patients are both genetically and clinically distinct phenotypes. © 2013 Springer Science+Business Media New York.
Created from Fastlane, Scopus look-up
Keywords: ACPA; Anti-citrullinated protein antibodies; Autoantibodies; Bone loss; Rheumatoid arthritis

A crucial role for Jagunal homolog 1 in humoral immunity and antibody glycosylation in mice and humans - Hagelkruys, Astrid; Wirnsberger, Gerald; Stadlmann, Johannes; Wöhner, Miriam; Horrer, Marion; Vilagos, Bojan; Jonsson, Gustav; Kogler, Melanie; Tortola, Luigi; Novatchkova, Maria; Bönelt, Peter; Hoffmann, David; et al. (Journal of Experimental Medicine, 2020)
Jagunal homolog 1 (JAGN1) has been identified as a critical regulator of neutrophil biology in mutant mice and rare-disease patients carrying JAGN1 mutations. Here, we report that Jagn1 deficiency results in alterations in the endoplasmic reticulum (ER) of antibody-producing cells as well as decreased antibody production and secretion. Consequently, mice lacking Jagn1 in B cells exhibit reduced serum immunoglobulin (Ig) levels at steady state and fail to mount an efficient humoral immune response upon immunization with specific antigens or when challenged with viral infections. We also demonstrate that Jagn1 deficiency in B cells results in aberrant IgG N-glycosylation leading to enhanced Fc receptor binding. Jagn1 deficiency in particular affects fucosylation of IgG subtypes in mice as well as rare-disease patients with loss-of-function mutations in JAGN1. Moreover, we show that ER stress affects antibody glycosylation. Our data uncover a novel and key role for JAGN1 and ER stress in antibody glycosylation and humoral immunity in mice and humans.
CRIS-Team Scopus Importer:2020-10-16

Affinity purified anti-citrullinated protein/peptide antibodies target antigens expressed in the rheumatoid joint - Ossipova, Elena; Cerqueira, Catia Fernandes; Reed, Evan; Kharlamova, Nastya; Israelsson, Lena; Holmdahl, Rikard; Nandakumar, Kutty Selva; Engstrom, Marianne; Harre, Ulrike; Schett, Georg; Catrina, Anca I.; Malmstrom, Vivianne; et al. (Arthritis Research & Therapy, 2014)
A major subset of patients with rheumatoid arthritis (RA) is characterized by the presence of circulating autoantibodies directed to citrullinated proteins/peptides (ACPAs). These autoantibodies, which are commonly detected by using an enzyme-linked immunosorbent assay (ELISA) based on synthetic cyclic citrullinated peptides (CCPs), predict clinical onset and a destructive disease course. In the present study, we have used plasma and synovial fluids from patients with RA, for the affinity purification and characterization of anti-CCP2 reactive antibodies, with an aim to generate molecular tools that can be used in vitro and in vivo for future investigations into the pathobiology of the ACPA response. Specifically, this study aims to demonstrate that the surrogate marker CCP2 can capture ACPAs that bind to autoantigens expressed in vivo in the major inflammatory lesions of RA (that is, in the rheumatoid joint).Plasma (n = 16) and synovial fluid (n = 26) samples were collected from RA patients with anti-CCP2 IgG levels of above 300 AU/mL. Total IgG was isolated on Protein G columns and subsequently applied to CCP2 affinity columns. Purified anti-CCP2 IgG was analyzed for reactivity and specificity by using the CCPlus® ELISA, in-house peptide ELISAs, Western blot, and immunohisto-/immunocytochemistry.Approximately 2% of the total IgG pool in both plasma and synovial fluid was CCP2-reactive. Purified anti-CCP2 reactive antibodies from different patients showed differences in binding to CCP2 and differences in binding to citrullinated peptides from ?-enolase, vimentin, fibrinogen, and collagen type II, illustrating different ACPA fine-specificity profiles. Furthermore, the purified ACPA bound not only in vitro citrullinated proteins but, more importantly, in vivo-generated epitopes on synovial fluid cells and synovial tissues from patients with RA.We have isolated ACPAs from plasma and synovial fluid and demonstrated that the CCP2 peptides, frequently used in diagnostic ELISAs, de facto act as surrogate antigens for at least four different, well-characterized, largely non-cross-reactive, ACPA fine specificities. Moreover, we have determined the concentration and proportion of CCP2-reactive IgG molecules in rheumatoid plasma and synovial fluid, and we have shown that the purified ACPAs can be used to detect both in vitro- and in vivo-generated citrullinated epitopes by various techniques. We anticipate that these antibodies will provide us with new opportunities to investigate the potential pathogenic effects of human ACPAs.
EVALuna2:12981

AKAP6 orchestrates the nuclear envelope microtubule-organizing center by linking golgi and nucleus via AKAP9 - Vergarajauregui, Silvia; Becker, Robert; Steffen, Ulrike; Sharkova, Maria; Esser, Tilman; Petzold, Jana; Billing, Florian; Kapiloff, Michael S.; Schett, Georg; Thievessen, Ingo; Engel, Felix (eLife, 2020)
The switch from centrosomal microtubule-organizing centers (MTOCs) to noncentrosomal MTOCs during differentiation is poorly understood. Here, we identify AKAP6 as key component of the nuclear envelope MTOC. In rat cardiomyocytes, AKAP6 anchors centrosomal proteins to the nuclear envelope through its spectrin repeats, acting as an adaptor between nesprin-1 alpha and Pcnt or AKAP9. In addition, AKAP6 and AKAP9 form a protein platform tethering the Golgi to the nucleus. Both Golgi and nuclear envelope exhibit MTOC activity utilizing either AKAP9, or Pcnt-AKAP9, respectively. AKAP6 is also required for formation and activity of the nuclear envelope MTOC in human osteoclasts. Moreover, ectopic expression of AKAP6 in epithelial cells is sufficient to recruit endogenous centrosomal proteins. Finally, AKAP6 is required for cardiomyocyte hypertrophy and osteoclast bone resorption activity. Collectively, we decipher the MTOC at the nuclear envelope as a bi-layered structure generating two pools of microtubules with AKAP6 as a key organizer.
CRIS-Team WoS Importer:2021-01-01

A new platform for autoimmune diseases. Inducing tolerance with liposomes encapsulating autoantigens - Almenara-Fuentes, Lidia; Rodriguez-Fernandez, Silvia; Rosell-Mases, Estela; Kachler, Katerina; You, Axel; Salvado, Miriam; Andreev, Darja; Steffen, Ulrike; Bang, Holger; Bozec, Aline; Schett, Georg; Le Panse, Rozen; et al. (Nanomedicine : nanotechnology, biology, and medicine, 2023)
Autoimmune diseases (AIDs) are caused by the loss of self-tolerance and destruction of tissues by the host's immune system. Several antigen-specific immunotherapies, focused on arresting the autoimmune attack, have been tested in clinical trials with discouraging results. Therefore, there is a need for innovative strategies to restore self-tolerance safely and definitively in AIDs. We previously demonstrated the therapeutic efficacy of phosphatidylserine (PS)-liposomes encapsulating autoantigens in experimental type 1 diabetes and multiple sclerosis. Here, we show that PS-liposomes can be adapted to other autoimmune diseases by simply replacing the encapsulated autoantigen. After administration, they are distributed to target organs, captured by phagocytes and interact with several immune cells, thus exerting a tolerogenic and immunoregulatory effect. Specific PS-liposomes demonstrate great preventive and therapeutic efficacy in rheumatoid arthritis and myasthenia gravis. Thus, this work highlights the therapeutic potential of a platform for several autoimmunity settings, which is specific, safe, and with long-term effects.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Autoimmune diseases; Immunotherapy; Myasthenia gravis; Nanomedicine; Preclinical mouse models; Rheumatoid arthritis

Antibodies against citrullinated proteins of IgA isotype are associated with progression to rheumatoid arthritis in individuals at-risk. - Sokolova, Maria; Hartmann, Fabian; Sieghart, Daniela; Bang, Holger; Steiner, Guenter; Kleyer, Arnd; Schett, Georg; Steffen, Ulrike (RMD Open, 2023)
OBJECTIVE: Events triggering disease outbreak in individuals at-risk for rheumatoid arthritis (RA at-risk) remain unclear, and the role of the various anticitrullinated protein antibody (ACPA) isotypes in this process is still to be established. We aimed to investigate the prevalence of IgA ACPA in RA at-risk individuals, their role in the transition from the RA at-risk status to RA and their dynamics during this transition. METHODS: Cross-sectional measurement of serum IgA1 and IgA2 ACPA levels was conducted in healthy controls, RA at-risk individuals and patients with RA and compared with the frequency of RA development in at risk individuals during a follow-up of 14 months. In addition, longitudinal measurements of serum IgA1 and IgA2 ACPA levels prior to, at and after the onset of RA were performed. RESULTS: Approximately two-thirds of RA at-risk individuals were positive for serum IgA1 and IgA2 ACPA in levels comparable to IgG ACPA positive patients with RA. IgA1, but not IgA2 ACPA positivity was associated with the transition from the RA at-risk state to RA within the following 14 months. Interestingly, during this transition process, IgA1 ACPA levels declined at RA onset and also thereafter during the early phase of RA. This decline was confirmed in a second, independent cohort. CONCLUSION: Both IgA1 and IgA2 ACPA are present in RA at-risk individuals, but only IgA1 ACPA are associated with the progression to RA. The observed decline in serum IgA1 ACPA levels before the onset of RA might indicate starting barrier leakiness prior to disease outbreak.
EVALuna2:520716

Association of a coding polymorphism in Fc gamma receptor 2A and graft survival in re-transplant candidates - Fuernrohr, Barbara G.; Weiss, Katrin M.; Harre, Ulrike; Wiesener, Michael; Spriewald, Bernd M.; Arnold, Martin (Human Immunology, 2015)
The family of Fc gamma receptors (Fc?Rs) is involved in mediating immunological effector functions. Fc?Rs are differentially expressed on immune cells and can act either activating or inhibitory, with Fc?R2A belonging to the first group. The polymorphism H131R (rs1801274) in FCGR2A has been associated with acute rejection and can shift the overall balance between activating and inhibitory Fc?Rs. Anti-HLA allo-antibodies in transplant recipients have been identified as risk factor for organ survival after transplantation. In this study we genotyped FCGR2A H131R in 200 patients who had undergone kidney transplantation and experienced loss of graft function. FCGR2A polymorphism was related to graft survival and anti-HLA antibodies. Graft survival was calculated as the time interval between transplantation and return to chronic dialysis after transplantation. The gene frequency of FCGR2A R/R131 was found significantly more often in patients with earlier (?60months) compared to patients with later (>60months) graft failure. Overall patients homozygous for R/R131 had a significantly shorter graft survival, compared to H/H131 or H/R131 which is even more pronounced, when anti-HLA antibodies were present. These data suggest, that FCGR2A polymorphisms constitute a risk factor for graft loss following kidney transplantation and that this effect is related to anti-HLA antibodie
EVALuna2:3812

ASSOCIATION OF ANTI-CITRULLINATED PROTEIN ANTIBODIES OF IgA SUBCLASSES WITH SUSTAINED REMISSION AND FLARE IN RHEUMATOID ARTHRITIS - Sokolova, Maria; Rech, Jürgen; Hagen, Melanie; Schett, Georg; Steffen, Ulrike (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-09-24

Autoantibodies in Rheumatoid Arthritis: Historical Background and Novel Findings - Sokolova, Maria; Schett, Georg; Steffen, Ulrike (Clinical Reviews in Allergy & Immunology, 2021)
Autoantibodies represent a hallmark of rheumatoid arthritis (RA), with the rheumatoid factor (RF) and antibodies against citrullinated proteins (ACPA) being the most acknowledged ones. RA patients who are positive for RF and/or ACPA (“seropositive”) in general display a different etiology and disease course compared to so-called “seronegative” patients. Still, the seronegative patient population is very heterogeneous and not well characterized. Due to the identification of new autoantibodies and advancements in the diagnosis of rheumatic diseases in the last years, the group of seronegative patients is constantly shrinking. Aside from antibodies towards various post-translational modifications, recent studies describe autoantibodies targeting some native proteins, further broadening the spectrum of recognized antigens. Next to the detection of new autoantibody groups, much research has been done to answer the question if and how autoantibodies contribute to the pathogenesis of RA. Since autoantibodies can be detected years prior to RA onset, it is a matter of debate whether their presence alone is sufficient to trigger the disease. Nevertheless, there is gathering evidence of direct autoantibody effector functions, such as stimulation of osteoclastogenesis and synovial fibroblast migration in in vitro experiments. In addition, autoantibody positive patients display a worse clinical course and stronger radiographic progression. In this review, we discuss current findings regarding different autoantibody types, the underlying disease-driving mechanisms, the role of Fab and Fc glycosylation and clinical implications.
CRIS-Team Scopus Importer:2021-09-17
Keywords: ACPA; Autoimmunity; Immunoglobulin; Rheumatoid arthritis

Autoantibody-mediated bone loss - Harre, Ulrike; Kittan, Nicolai A.; Schett, Georg (Current Osteoporosis Reports, 2014)
In rheumatoid arthritis (RA), the presence of autoantibodies such as the rheumatoid factor and antibodies against citrullinated proteins is highly correlated with the severity of disease and bone loss. For many years, the involvement of autoantibodies in bone resorption has merely been attributed to enhanced tissue infiltration and the production of inflammatory cytokines that promote osteoclastogenesis. However, recent research provides evidence for a direct activation of osteoclasts and their precursors by autoantibodies, which is independent of inflammation. The depletion of B-cells with rituximab that substantially reduces autoantibody levels seems to be as effective as the well-established treatment with tumor necrosis factor-antagonists in RA patients that do not respond to methotrexate, highlighting the significance of autoantibodies for RA and bone los
EVALuna2:12934

Blockade of IL-36 Receptor Signaling Does Not Prevent from TNF-Induced Arthritis - Derer, Anja; Groetsch, Bettina; Harre, Ulrike; Böhm, Christina; Towne, Jennifer; Schett, Georg; Frey, Silke; Hueber, Axel (PLoS ONE, 2014)
Interleukin (IL)-36? is a newly described member of the IL-1 cytokine family with a known inflammatory and pathogenic function in psoriasis. Recently, we could demonstrate that the receptor (IL-36R), its ligand IL-36? and its antagonist IL-36Ra are expressed in synovial tissue of arthritis patients. Furthermore, IL-36? induces MAP-kinase and NF?B signaling in human synovial fibroblasts with subsequent expression and secretion of pro-inflammatory cytokines.To understand the pathomechanism of IL-36 dependent inflammation, we investigated the biological impact of IL-36? signaling in the hTNFtg mouse. Also the impact on osteoclastogenesis by IL-36? was tested in murine and human osteoclast assays.Diseased mice showed an increased expression of IL-36R and IL-36? in inflamed knee joints compared to wildtype controls. However, preventively treating mice with an IL-36R blocking antibody led to no changes in clinical onset and pattern of disease. Furthermore, blockade of IL-36 signaling did not change histological signs of TNF-induced arthritis. Additionally, no alteration on bone homeostasis was observed in ex vivo murine and human osteoclast differentiation assays.Thus we conclude that IL-36? does not affect the development of inflammatory arthriti
EVALuna2:12991

Bone Loss Before Clinical Onset of Rheumatoid Arthritis o Subjects with Anti-Citrullinated Protein Antibodies - Finzel, Stephanie; Lang, Veronika; Kleyer, Arnd; Rech, Jürgen; Manger, Bernhard; Guilhon de Araujo, Elizabeth; Hueber, Axel; Harre, Ulrike; Schett, Georg (2012)
EVALuna2:34465

Bone loss before the clinical onset of rheumatoid arthritis in subjects with anticitrullinated protein antibodies - Kleyer, Arnd; Finzel, Stephanie; Rech, Jürgen; Manger, Bernhard; Krieter, Manuel; Faustini, Francesca; Araujo, Elisabeth; Hueber, Axel; Harre, Ulrike; Engelke, Klaus; Schett, Georg (Annals of the Rheumatic Diseases, 2014)
Anticitrullinated protein antibodies (ACPA) are a major risk factor for bone loss in rheumatoid arthritis (RA). We have recently shown that ACPA directly induce bone loss by stimulating osteoclast differentiation. As ACPA precede the clinical onset of RA by years, we hypothesised that ACPA positive healthy individuals may already show skeletal changes.We performed a comparative micro-CT analysis of the bone microstructure in the metacarpophalangeal joints of ACPA positive and ACPA negative healthy individuals without clinical signs of arthritis.ACPA positive (n=15) and negative (n=15) healthy individuals were not different in age (48.2±4.1 vs 51.4±3.8 years, p=0.57) or gender (eight women and two men in both groups). Bone mineral density was significantly reduced in ACPA positive individuals (mean±SEM 280±11 mg/cm(3)) compared with controls (327±6). Bone loss was based on cortical bone changes, with significant (p=0.044) reduction in cortical thickness in the ACPA positive group (mean±SEM 0.22±0.03 mm) compared with controls (0.32±0.03 mm). Areas of cortical porosity were significantly (p=0.0005) more widespread in ACPA positive (mean±SEM 7.4±1.4%) than in ACPA negative individuals (1.0±0.3%).Structural bone damage starts before the clinical onset of arthritis in subjects with ACPA. These findings revise the concept that bone damage is an exclusive consequence of synovitis in patients with R
EVALuna2:10080

Caspase-8 promotes scramblase-mediated phosphatidylserine exposure and fusion of osteoclast precursors - Krishnacoumar, Brenda; Stenzel, Martin; Garibagaoglu, Hilal; Omata, Yasunori; Sworn, Rachel L.; Hofmann, Thea; Ipseiz, Natacha; Czubala, Magdalena A.; Steffen, Ulrike; Maccataio, Antonio; Stoll, Cornelia; Böhm, Christina; et al. (Bone Research, 2024)
Efficient cellular fusion of mononuclear precursors is the prerequisite for the generation of fully functional multinucleated bone-resorbing osteoclasts. However, the exact molecular factors and mechanisms controlling osteoclast fusion remain incompletely understood. Here we identify RANKL-mediated activation of caspase-8 as early key event during osteoclast fusion. Single cell RNA sequencing-based analyses suggested that activation of parts of the apoptotic machinery accompanied the differentiation of osteoclast precursors into mature multinucleated osteoclasts. A subsequent characterization of osteoclast precursors confirmed that RANKL-mediated activation of caspase-8 promoted the non-apoptotic cleavage and activation of downstream effector caspases that translocated to the plasma membrane where they triggered activation of the phospholipid scramblase Xkr8. Xkr8-mediated exposure of phosphatidylserine, in turn, aided cellular fusion of osteoclast precursors and thereby allowed generation of functional multinucleated osteoclast syncytia and initiation of bone resorption. Pharmacological blockage or genetic deletion of caspase-8 accordingly interfered with fusion of osteoclasts and bone resorption resulting in increased bone mass in mice carrying a conditional deletion of caspase-8 in mononuclear osteoclast precursors. These data identify a novel pathway controlling osteoclast biology and bone turnover with the potential to serve as target for therapeutic intervention during diseases characterized by pathologic osteoclast-mediated bone loss. (Figure presented.)
CRIS-Team Scopus Importer:2024-07-19

Cellular and molecular pathways of structural damage in rheumatoid arthritis - Harre, Ulrike; Schett, Georg (Seminars in Immunopathology, 2017)
Structural damage of cartilage and bone tissue is a hallmark of rheumatoid arthritis (RA). The resulting joint destruction constitutes one of the major disease consequences for patients and creates a significant burden for the society. The main cells executing bone and cartilage degradation are osteoclasts and fibroblast-like synoviocytes, respectively. The function of both cell types is heavily influenced by the immune system. In the last decades, research has identified several mediators of structural damage, ranging from infiltrating immune cells and inflammatory cytokines to autoantibodies. These factors result in an inflammatory milieu in the affected joints which leads to an increased development and function of osteoclasts and the transformation of fibroblast-like synoviocytes towards a highly migratory and destructive phenotype. In addition, repair mechanisms mediated by osteoblasts and chondrocytes are strongly impaired by the presence of pro-inflammatory cytokines. This article will review the current knowledge on the mechanisms of joint inflammation and the destruction of bone and cartilag
EVALuna2:13301

Correlation of Anti-HLA IgA Alloantibodies and Fc Receptor Motives with Kidney Allograft Survival - Arnold, Martin; Steffen, Ulrike; Wiesener, Michael; Bach, Christian; Spriewald, Bernd; Lindemann, Monika (Immuno, 2022)
Immunoglobulin A (IgA) is the most abundant antibody isotype in humans and anti-HLA IgA was found in sera of transplant recipients. Focusing on patients awaiting kidney re-transplantation, we tested the impact of anti-HLA-class I/II IgA antibodies on graft survival. We analyzed 276 patients with and 238 without allograft failure. Eight motives of the Fcα receptor (FCAR) and Fcγ receptor were analyzed in patients with allograft failure. The distribution of anti-HLA IgA1/A2 and IgG antibodies differed significantly (p < 0.0001) between both patient groups, and IgA1 plus IgA2 antibodies were more abundant in patients with allograft failure. Allograft survival was significantly impaired if anti-HLA-class I plus II IgA was present, in the first 105 months (9 years) of follow-up (median of 43 vs. >105 months, p = 0.007). Patients with anti-HLA IgA and IgG vs. anti-HLA IgG only had a significantly shorter allograft survival within that follow-up period (88 vs. >105 months, p = 0.008). Moreover, allograft survival was shorter (p = 0.02) in carriers of GG vs. AA + AG genotypes of FCAR rs16986050. Thus, the presence of anti-HLA IgA plus IgG vs. IgG only was associated with shorter kidney allograft survival and FCAR motives may impact on graft survival.
CRIS-Team Scopus Importer:2024-12-16
Keywords: antibodies; Fcα receptor polymorphism; Fcγ receptor polymorphism; graft survival; immunoglobulin isotypes; transplantation

Effects of Autoantibodies on Osteoclasts - Sokolova, Maria; Steffen, Ulrike (Osteologie, 2021)
The balance between bone forming osteoblasts and bone resorbing osteoclasts can be disturbed in autoimmune diseases resulting in local and systemic bone loss. It was long time believed that autoantibodies only indirectly contribute to bone loss by fueling the overall inflammation. However, in the last decade, more and more evidence emerged that autoantibodies and immune complexes directly activate osteoclasts and pre-osteoclasts by binding to Fc gamma receptors (Fc gamma Rs) on the (pre)osteoclast cell surface. This pro-osteoclastogenic effect seems to be dependent on the absence of sialic acid in the IgG Fc glycan, which is a typical feature of many autoantibodies. Clinical studies revealed the importance of autoantibody-mediated bone loss mainly in rheumatoid arthritis, but also in other diseases, such as celiac disease. In summary, the gained knowledge about autoantibody-mediated bone loss helps to better understand bone pathologies of autoimmune diseases. However, studies are still relatively limited and more research is needed to fully understand the impact of autoantibodies on bone and to develop future therapeutic strategies.
CRIS-Team WoS Importer:2021-10-08

Estrogen induces St6gal1 expression and increases IgG sialylation in mice and patients with rheumatoid arthritis: a potential explanation for the increased risk of rheumatoid arthritis in postmenopausal women - Engdahl, Cecilia; Bondt, Albert; Harre, Ulrike; Raufer, Jasmin; Pfeifle, Rene; Camponeschi, Alessandro; Wuhrer, Manfred; Seeling, Michaela; Martensson, Inga-Lill; Nimmerjahn, Falk; Krönke, Gerhard; Scherer, Hans U.; et al. (Arthritis Research & Therapy, 2018)
BACKGROUND: Rheumatoid arthritis (RA) preferentially affects women, with the peak incidence coinciding with estrogen decrease in menopause. Estrogen (E2) may therefore have intrinsic immune-regulatory properties that vanish with menopause. Fc sialylation is a crucial factor determining the inflammatory effector function of antibodies. We therefore analyzed whether E2 affects immunoglobulin G (IgG) sialylation. METHODS: Postmenopausal (ovariectomized) mice were immunized with ovalbumin and treated with E2 or vehicle. Total and ovalbumin-specific IgG concentrations, sialylation, and Fcγ receptor expression were analyzed. Postmenopausal women with RA receiving hormone replacement therapy, including E2, or no treatment were analyzed for IgG sialylation. Furthermore, effects of E2 on the expression of the sialylation enzyme β-galactoside α2,6-sialyltransferase 1 (St6Gal1) were studied in mouse and human antibody-producing cells. RESULTS: E2 treatment significantly increased Fc sialylation of total and ovalbumin-specific IgG in postmenopausal mice. Furthermore, E2 led to increased expression of inhibitory Fcγ receptor IIb on bone marrow leukocytes. Treatment with E2 also increased St6Gal1 expression in mouse and human antibody-producing cells, providing a mechanistic explanation for the increase in IgG-Fc sialylation. In postmenopausal women with RA, treatment with E2 significantly increased the Fc sialylation of IgG. CONCLUSIONS: E2 induces anti-inflammatory effector functions in IgG by inducing St6Gal1 expression in antibody-producing cells and by increasing Fc sialylation. These observations provide a mechanistic explanation for the increased risk of RA in conditions with low estrogen levels such as menopause.
EVALuna2:34145

ESTROGEN INFLUENCES THE SIALYLATION PROFILE AND INFLAMMATORY PROPERTIES OF ANTIBODIES - A POTENTIAL EXPLANATION FOR THE SEX DIFFERENCES AND INCREASED RISK FOR RA IN POSTMENOPAUSAL WOMEN - Engdahl, C.; Raufer, Jasmin; Harre, Ulrike; Bondt, A.; Pfeifle, René; Krönke, Gerhard; Scherer, H. U.; Forsblad, H.; Schett, Georg (2017)
EVALuna2:35033

Ethanol consumption decreases autoantibody titers by blocking IL-21 secretion of Tfh cells during the development of arthritis - Azizov, Vugar; Dietel, K.; Kolenbrander, A.; Seubert, S.; Steffen, F.; Meidenbauer, J.; Steffen, Ulrike; Hofmann, Jörg; Nimmerjahn, Falk; Linker, R.; Wirtz, Stefan; Sarter-Zaiss, Kerstin; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Ethanol consumption inhibits TFH cell responses and the development of autoimmune arthritis - Azizov, Vugar; Dietel, Katharina; Steffen, Franziska; Dürholz, Kerstin; Meidenbauer, Julia; Lucas, Sébastien; Frech, Michael; Omata, Yasunori; Tajik, Narges; Knipfer, Lisa; Kolenbrander, Anne; Seubert, Silvia; et al. (Nature Communications, 2020)
Alcohol consumption is a consistent protective factor for the development of autoimmune diseases such as rheumatoid arthritis (RA). The underlying mechanism for this tolerance-inducing effect of alcohol, however, is unknown. Here we show that alcohol and its metabolite acetate alter the functional state of T follicular helper (TFH) cells in vitro and in vivo, thereby exerting immune regulatory and tolerance-inducing properties. Alcohol-exposed mice have reduced Bcl6 and PD-1 expression as well as IL-21 production by TFH cells, preventing proper spatial organization of TFH cells to form TFH:B cell conjugates in germinal centers. This effect is associated with impaired autoantibody formation, and mitigates experimental autoimmune arthritis. By contrast, T cell independent immune responses and passive models of arthritis are not affected by alcohol exposure. These data clarify the immune regulatory and tolerance-inducing effect of alcohol consumption.
CRIS-Team Scopus Importer:2020-05-05

Ethanol consumption inhibits the development of autoimmunity by blocking IL-21 secretion in T-FH cells - Azizov, Vugar; Dietel, K.; Kolenbrander, A.; Seubert, S.; Steffen, F.; Meidenbauer, J.; Steffen, Ulrike; Hofmann, J.; Nimmerjahn, Falk; Linker, R.; Wirtz, Stefan; Herrmann, Martin; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-05

Galectin-3 as a novel regulator of osteoblast-osteoclast interaction and bone homeostasis - Simon, Dominic; Derer, Anja; Andes, Fabian T.; Lezuo, Patrick; Bozec, Aline; Schett, Georg; Herrmann, Martin; Harre, Ulrike (Bone, 2017)
Bone tissue undergoes permanent and lifelong remodeling with a concerted action of bone-building osteoblasts and bone-resorbing osteoclasts. A precise cooperation between those two cell types is critical in the complex process of bone renewal. Galectin-3 is a member of the ?-galactoside-binding lectin family playing multiple roles in cell growth, differentiation and aggregation. As it has been described to be expressed in bone, galectin-3 might influence bone homeostasis by regulating the function and/or interplay of osteoblasts and osteoclasts. Here, we investigated the role of galectin-3 in osteoclastogenesis and osteoblast-osteoclast interactions. Bone histomorphometric analysis and ?CT measurements revealed a decreased trabecular bone volume and an increased osteoclast number in 12weeks old male galectin-3 knockout mice compared to wildtype littermates. Galectin-3 deficient bone marrow cells displayed a higher osteoclastogenic capacity in ex vivo differentiation assays, associated with elevated TRAF6 mRNA levels, suggesting an intrinsic inhibition of osteoclastogenesis by galectin-3 interfering with RANKL-mediated signaling. Furthermore, the addition of extracellular galectin-3 to murine or human osteoclastogenesis assays inhibited osteoclast formation and osteoclast numbers were higher in co-culture assays with galectin-3 deficient osteoblasts. In conclusion, our data suggest the secretion of galectin-3 as a novel mechanism for osteoblasts to control osteoclastogenesis and to maintain trabecular bone homeostasis independently of the RANKL/OPG-axis.
EVALuna2:13345

Generation and Analysis of Human and Murine Osteoclasts - Steffen, Ulrike; Andes, Fabian T.; Schett, Georg (Current Protocols in Immunology, 2019)
Osteoclasts are the only bone-resorbing cells in the body. Together with bone-forming osteoblasts, they are responsible for bone homeostasis and constant bone remodeling. Aberrant activation of osteoclasts leads to bone loss, as seen in postmenopausal osteoporosis or in autoimmune diseases like rheumatoid arthritis. Although much research has been performed to understand and prevent osteoclast-mediated bone loss, the mechanisms of osteoclast hyperactivation are not completely understood. This unit describes several protocols for ex vivo generation of murine and human osteoclasts, allowing study of the effects of specific cells, cytokines, or chemical substances on osteoclast formation and activity without the need for expensive and time-consuming animal experiments. In addition, we provide protocols for specific staining of osteoclasts and for analysis of resorption activity using calcium phosphate–coated surfaces or bone slices. © 2019 by John Wiley & Sons, Inc.
CRIS-Team Scopus Importer:2019-06-21
Keywords: bone marrow; osteoclast generation; PBMC; resorption; TRAP staining

Glycosylation of immunoglobulin G determines osteoclast differentiation and bone loss. - Harre, Ulrike; Lang, Stefanie; Pfeifle, René; Rombouts, Yoann; Frühbeißer, Sabine; Amara, Khaled; Bang, Holger; Lux, Anja; Koeleman, Carolien A.; Baum, Wolfgang; Dietel, Katharina; Gröhn, Franziska; et al. (Nature Communications, 2015)
Immunglobulin G (IgG) sialylation represents a key checkpoint that determines the engagement of pro- or anti-inflammatory Fcγ receptors (FcγR) and the direction of the immune response. Whether IgG sialylation influences osteoclast differentiation and subsequently bone architecture has not been determined yet, but may represent an important link between immune activation and bone loss. Here we demonstrate that desialylated, but not sialylated, immune complexes enhance osteoclastogenesis in vitro and in vivo. Furthermore, we find that the Fc sialylation state of random IgG and specific IgG autoantibodies determines bone architecture in patients with rheumatoid arthritis. In accordance with these findings, mice treated with the sialic acid precursor N-acetylmannosamine (ManNAc), which results in increased IgG sialylation, are less susceptible to inflammatory bone loss. Taken together, our findings provide a novel mechanism by which immune responses influence the human skeleton and an innovative treatment approach to inhibit immune-mediated bone los

How Autoantibodies Regulate Osteoclast Induced Bone Loss in Rheumatoid Arthritis - Steffen, Ulrike; Schett, Georg; Bozec, Aline (Frontiers in Immunology, 2019)
Rheumatoid arthritis (RA) is a chronic inflammatory disease, characterized by autoimmunity that triggers joint inflammation and tissue destruction. Traditional concepts of RA pathogenesis have strongly been focused on inflammation. However, more recent evidence suggests that autoimmunity per se modulates the disease and in particular bone destruction during the course of RA. RA-associated bone loss is caused by increased osteoclast differentiation and activity leading to rapid bone resorption. Autoimmunity in RA is based on autoantibodies such as rheumatoid factor (RF) and autoantibodies against citrullinated proteins (ACPA). These autoantibodies exert effector functions on immune cells and on bone resorbing osteoclasts, thereby facilitating bone loss. This review summarizes potential pathways involved in increased destruction of bone tissue in RA, particularly focusing on the direct and indirect actions of autoantibodies on osteoclast generation and function.
CRIS-Team WoS Importer:2019-07-16

Humoral and Cellular Immune Responses to SARS–CoV-2 Infection and Vaccination in Autoimmune Disease Patients With B Cell Depletion - Simon, David; Tascilar, Koray; Schmidt, Katja; Manger, Bernhard; Weckwerth, Leonie; Sokolova, Maria; Bucci, Laura; Fagni, Filippo; Manger, Karin; Schuch, Florian; Ronneberger, Monika; Hueber, Axel; et al. (Arthritis and Rheumatology, 2021)
Objective: B cell depletion is an established therapeutic principle in a wide range of autoimmune diseases. However, B cells are also critical for inducing protective immunity after infection and vaccination. We undertook this study to assess humoral and cellular immune responses after infection with or vaccination against SARS–CoV-2 in patients with B cell depletion and controls who are B cell–competent. Methods: Antibody responses (tested using enzyme-linked immunosorbent assay) and T cell responses (tested using interferon-γ enzyme-linked immunospot assay) against the SARS–CoV-2 spike S1 and nucleocapsid proteins were assessed in a limited number of previously infected (n = 6) and vaccinated (n = 8) autoimmune disease patients with B cell depletion, as well as previously infected (n = 30) and vaccinated (n = 30) healthy controls. Results: As expected, B cell and T cell responses to the nucleocapsid protein were observed only after infection, while respective responses to SARS–CoV-2 spike S1 were found after both infection and vaccination. A SARS–CoV-2 antibody response was observed in all vaccinated controls (30 of 30 [100%]) but in none of the vaccinated patients with B cell depletion (0 of 8). In contrast, after SARS–CoV-2 infection, both the patients with B cell depletion (spike S1, 5 of 6 [83%]; nucleocapsid, 3 of 6 [50%]) and healthy controls (spike S1, 28 of 30 [93%]; nucleocapsid, 28 of 30 [93%]) developed antibodies. T cell responses against the spike S1 and nucleocapsid proteins were found in both infected and vaccinated patients with B cell depletion and in the controls. Conclusion: These data show that B cell depletion completely blocks humoral but not T cell SARS–CoV-2 vaccination response. Furthermore, limited humoral immune responses are found after SARS–CoV-2 infection in patients with B cell depletion.
CRIS-Team Scopus Importer:2021-12-03

IgA2 Antibodies against SARS-CoV-2 Correlate with NET Formation and Fatal Outcome in Severely Diseased COVID-19 Patients - Staats, Leonie A. N.; Pfeiffer, Hella; Knopf, Jasmin; Lindemann, Aylin; Fürst, Julia; Kremer, Andreas; Hackstein, Holger; Neurath, Markus; Munoz, Luis Enrique; Achenbach, Susanne; Leppkes, Moritz; Herrmann, Martin; et al. (Cells, 2020)
Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) leads to an adaptive immune response in the host and the formation of anti-SARS-CoV-2 specific antibodies. While IgG responses against SARS-CoV-2 have been characterized quite well, less is known about IgA. IgA2 activates immune cells and induces inflammation and neutrophil extracellular trap (NET) formation which may contribute to organ injury and fatal outcome in SARS-CoV-2-infected patients. SARS-CoV-2 spike protein specific antibody levels were measured in plasma samples of 15 noninfected controls and 82 SARS-CoV-2-infected patients with no or mild symptoms, moderate symptoms (hospitalization) or severe disease (intensive care unit, ICU). Antibody levels were compared to levels of C-reactive protein (CRP) and circulating extracellular DNA (ecDNA) as markers for general inflammation and NET formation, respectively. While levels of SARS-CoV-2-specific IgG were similar in all patient groups, IgA2 antibodies were restricted to severe disease and showed the strongest discrimination between nonfatal and fatal outcome in patients with severe SARS-CoV-2 infection. While anti-SARS-CoV-2 IgG and IgA2 levels correlated with CRP levels in severely diseased patients, only anti-SARS-CoV-2 IgA2 correlated with ecDNA. These data suggest that the formation of anti-SARS-CoV-2 IgA2 during SARS-CoV-2 infection is a marker for more severe disease related to NET formation and poor outcome.
CRIS-Team WoS Importer:2021-01-15

IgA2 immune complexes selectively promote inflammation by human CD103+ dendritic cells - Mes, Lynn; Steffen, Ulrike; Chen, Hung-Jen; Veth, Jennifer; Hoepel, Willianne; Griffith, Guillermo Romeo; Schett, Georg; Den Dunnen, Jeroen (Frontiers in Immunology, 2023)
While immunoglobulin A (IgA) is well known for its neutralizing and anti-inflammatory function, it is becoming increasingly clear that IgA can also induce human inflammatory responses by various different immune cells. Yet, little is known about the relative role of induction of inflammation by the two IgA subclasses i.e. IgA1, most prominent subclass in circulation, and IgA2, most prominent subclass in the lower intestine. Here, we set out to study the inflammatory function of IgA subclasses on different human myeloid immune cell subsets, including monocytes, and in vitro differentiated macrophages and intestinal CD103+ dendritic cells (DCs). While individual stimulation with IgA immune complexes only induced limited inflammatory responses by human immune cells, both IgA subclasses strongly amplified pro-inflammatory cytokine production upon co-stimulation with Toll-like receptor (TLR) ligands such as Pam3CSK4, PGN, and LPS. Strikingly, while IgA1 induced slightly higher or similar levels of pro-inflammatory cytokines by monocytes and macrophages, respectively, IgA2 induced substantially more inflammation than IgA1 by CD103+ DCs. In addition to pro-inflammatory cytokine proteins, IgA2 also induced higher mRNA expression levels, indicating that amplification of pro-inflammatory cytokine production is at least partially regulated at the level of gene transcription. Interestingly, cytokine amplification by IgA1 was almost completely dependent on Fc alpha receptor I (FcαRI), whilst blocking this receptor only partially reduced cytokine induction by IgA2. In addition, IgA2-induced amplification of pro-inflammatory cytokines was less dependent on signaling through the kinases Syk, PI3K, and TBK1/IKKϵ. Combined, these findings indicate that IgA2 immune complexes, which are most abundantly expressed in the lower intestine, particularly promote inflammation by human CD103+ intestinal DCs. This may serve an important physiological function upon infection, by enabling inflammatory responses by this otherwise tolerogenic DC subset. Since various inflammatory disorders are characterized by disturbances in IgA subclass balance, this may also play a role in the induction or exacerbation of chronic intestinal inflammation.
CRIS-Team Scopus Importer:2023-04-21
Keywords: CD103; FcαRI; IgA subclasses; inflammation; intestine

IGA ACPA ARE ASSOCIATED WITH PROGRESSION TO RHEUMATOID ARTHRITIS IN INDIVIDUALS AT-RISK AND DECLINE IN LEVELS AROUND THE DISEASE ONSET - Sokolova, Maria; Hartmann, F.; Sieghart, D.; Steiner, G.; Kleyer, Arnd; Schett, Georg; Steffen, Ulrike (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

IgA anti-citrullinated protein antibodies are associated with flares during DMARD tapering in rheumatoid arthritis. - Sokolova, Maria; Hagen, Melanie; Bang, Holger; Schett, Georg; Rech, Jürgen; Steffen, Ulrike (Rheumatology, 2022)
OBJECTIVES: A substantial proportion of RA patients flare upon withdrawal of DMARDs, and thus the definition of prognostic markers is crucial. ACPA positivity has been identified as a risk factor for flare. However, only the role of IgG ACPA is established in this context, while the role of IgA ACPA is poorly defined. We thus aimed to investigate the role of IgA ACPA in flaring of RA. METHODS: Serum levels of IgA1 and IgA2 ACPA at baseline and after 12 months were measured in 108 patients from the randomized controlled RETRO study. RA patients in stable remission for at least 6 months at study recruitment were assigned to either one of the DMARD tapering arms or to continuation of DMARDs. RESULTS: In patients remaining in remission but not in the ones who flared, IgA2 ACPA levels and proportion of IgA2 in ACPA (IgA2% ACPA) significantly declined (median of 17.5%; P < 0.0001). This seemed to be independent of the treatment choice, as there was no difference in IgA2 ACPA dynamics between the study arms. IgA2% ACPA was associated with disease activity (DAS28) at flare (r = 0.36; P = 0.046). IgA and IgG ACPA showed a tendency towards independent contribution to the risk of flare with the highest risk if a patient had both antibody classes. CONCLUSION: In this study, IgA ACPA was identified as a risk factor for flare in combination with IgG ACPA. IgA2 ACPA levels were associated with flare severity and declined in patients in stable remission.
EVALuna2:474284

IgA Complexes Induce Neutrophil Extracellular Trap Formation More Potently Than IgG Complexes - Gimpel, Anna; Maccataio, Antonio; Unterweger, Harald; Sokolova, Maria; Schett, Georg; Steffen, Ulrike (Frontiers in Immunology, 2022)
Neutrophil extracellular trap (NET) formation is a powerful instrument to fight pathogens, but may induce collateral damage in the affected tissues. Besides pathogen-derived factors, immune complexes are potent inducers of NET formation. Neutrophils express IgA and IgG specific Fc receptors (FcRs) and therefore respond to complexed IgA and IgG. Especially in the context of autoimmune diseases, IgA and IgG immune complexes have been shown to trigger NET formation, a process that putatively contributes to disease severity. However, it is of question if both antibody classes stimulate neutrophils to the same extent. In this study, we compared the capability of IgA and IgG complexes formed by heat aggregation to induce NET formation. While stimulation of neutrophils with IgA complexes robustly induced NET formation, complexed IgG only marginally increased the amount of NETs compared to the unstimulated control. Mixing IgA with IgG before heat aggregation did not increase the effect of complexed IgA on neutrophils. By contrast, the presence of IgG complexes seemed to disturb neutrophil stimulation by IgA complexes. The capacity of complexed IgG to induce NET formation could not be increased by the addition of autologous serum or the removal of terminal sialic acid in the Fc glycan. Together, our data show that IgA is a much more potent inducer of NET formation than IgG. IgA may thus be the main driving force in (auto)immune complex-mediated NET formation.
CRIS-Team Scopus Importer:2022-02-11
Keywords: IgA; IgG; immune complex; NET; neutrophil

IgA subclasses have different effector functions associated with distinct glycosylation profiles - Steffen, Ulrike; Koeleman, Carolien A.; Sokolova, Maria V.; Bang, Holger; Kleyer, Arnd; Rech, Jürgen; Unterweger, Harald; Schicht, Martin; Garreis, Fabian; Hahn, Jonas; Andes, Fabian T.; Hahn, Madelaine; et al. (Nature Communications, 2020)
Monomeric serum immunoglobulin A (IgA) can contribute to the development of various autoimmune diseases, but the regulation of serum IgA effector functions is not well defined. Here, we show that the two IgA subclasses (IgA1 and IgA2) differ in their effect on immune cells due to distinct binding and signaling properties. Whereas IgA2 acts pro-inflammatory on neutrophils and macrophages, IgA1 does not have pronounced effects. Moreover, IgA1 and IgA2 have different glycosylation profiles, with IgA1 possessing more sialic acid than IgA2. Removal of sialic acid increases the pro-inflammatory capacity of IgA1, making it comparable to IgA2. Of note, disease-specific autoantibodies in patients with rheumatoid arthritis display a shift toward the pro-inflammatory IgA2 subclass, which is associated with higher disease activity. Taken together, these data demonstrate that IgA effector functions depend on subclass and glycosylation, and that disturbances in subclass balance are associated with autoimmune disease.
CRIS-Team Scopus Importer:2020-01-21

Induction of osteoclastogenesis and bone loss by human autoantibodies against citrullinated vimentin. - Harre, Ulrike; Georgess, Dan; Bang, Holger; Bozec, Aline; Axmann, Roland; Ossipova, Elena; Jakobsson, Per-Johan; Baum, Wolfgang; Nimmerjahn, Falk; Szarka, Eszter; Sarmay, Gabriella; Krumbholz, Grit; et al. (Journal of Clinical Investigation, 2012)
Autoimmunity is complicated by bone loss. In human rheumatoid arthritis (RA), the most severe inflammatory joint disease, autoantibodies against citrullinated proteins are among the strongest risk factors for bone destruction. We therefore hypothesized that these autoantibodies directly influence bone metabolism. Here, we found a strong and specific association between autoantibodies against citrullinated proteins and serum markers for osteoclast-mediated bone resorption in RA patients. Moreover, human osteoclasts expressed enzymes eliciting protein citrullination, and specific N-terminal citrullination of vimentin was induced during osteoclast differentiation. Affinity-purified human autoantibodies against mutated citrullinated vimentin (MCV) not only bound to osteoclast surfaces, but also led to robust induction of osteoclastogenesis and bone-resorptive activity. Adoptive transfer of purified human MCV autoantibodies into mice induced osteopenia and increased osteoclastogenesis. This effect was based on the inducible release of TNF-α from osteoclast precursors and the subsequent increase of osteoclast precursor cell numbers with enhanced expression of activation and growth factor receptors. Our data thus suggest that autoantibody formation in response to citrullinated vimentin directly induces bone loss, providing a link between the adaptive immune system and bon

JAK inhibition increases bone mass in steady-state conditions and ameliorates pathological bone loss by stimulating osteoblast function - Adam, Susanne; Simon, Nils; Steffen, Ulrike; Andes, Fabian T.; Scholtysek, Carina; Müller, Dorothea; Weidner, Daniela; Andreev, Darja; Kleyer, Arnd; Culemann, Stephan; Hahn, Madelaine; Schett, Georg; et al. (Science Translational Medicine, 2020)
Janus kinase (JAK)-mediated cytokine signaling has emerged as an important therapeutic target for the treatment of inflammatory diseases such as rheumatoid arthritis (RA). Accordingly, JAK inhibitors compose a new class of drugs, among which tofacitinib and baricitinib have been approved for the treatment of RA. Periarticular bone erosions contribute considerably to the pathogenesis of RA. However, although the immunomodulatory aspect of JAK inhibition (JAKi) is well defined, the current knowledge of how JAKi influences bone homeostasis is limited. Here, we assessed the effects of the JAK inhibitors tofacitinib and baricitinib on bone phenotype (i) in mice during steady-state conditions or in mice with bone loss induced by (ii) estrogen-deficiency (ovariectomy) or (iii) inflammation (arthritis) to evaluate whether effects of JAKi on bone metabolism require noninflammatory/inflammatory challenge. In all three models, JAKi increased bone mass, consistent with reducing the ratio of receptor activator of NF-κB ligand/osteoprotegerin in serum. In vitro, effects of tofacitinib and baricitinib on osteoclast and osteoblast differentiation were analyzed. JAKi significantly increased osteoblast function (P < 0.05) but showed no direct effects on osteoclasts. Additionally, mRNA sequencing and ingenuity pathway analyses were performed in osteoblasts exposed to JAKi and revealed robust up-regulation of markers for osteoblast function, such as osteocalcin and Wnt signaling. The anabolic effect of JAKi was illustrated by the stabilization of β-catenin. In humans with RA, JAKi induced bone-anabolic effects as evidenced by repair of arthritic bone erosions. Results support that JAKi is a potent therapeutic tool for increasing osteoblast function and bone formation.
CRIS-Team Scopus Importer:2020-02-21

JAK-INHIBITORS TOFACITINIB AND BARICITINIB IMPROVE PATHOLOGICAL BONE LOSS IN VIVO - Adam, Susanne; Simon, Nils; Steffen, Ulrike; Harre, Nee; Andes, Fabian; Mueller, Dorothea; Culemann, Stephan; Andreev, Darja; Hahn, Madelaine; Scholtysek, Carina; Schett, Georg; Krönke, Gerhard; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-12

Moonlighting osteoclasts as undertakers of apoptotic cells - Harre, Ulrike; Keppeler, Hildegard; Ipseiz, Natacha; Derer, Anja; Poller, Kerstin; Aigner, Michael; Schett, Georg; Herrmann, Martin; Lauber, Kirsten (Autoimmunity, 2012)
Created from Fastlane, Scopus look-up
Keywords: Apoptotic cell clearance; Dying cell clearance; Efferocytosis; Osteoclasts; Phagocytosis; Rheumatoid arthritis

Neurodegeneration Enhances the Development of Arthritis - Lang, Stefanie; Harre, Ulrike; Purohit, Pavitra; Dietel, Katharina; Kienhöfer, Deborah; Hahn, Jonas; Baum, Wolfgang; Herrmann, Martin; Schett, Georg; Mielenz, Dirk (Journal of Immunology, 2017)
The prevalence of neurodegenerative disease and arthritis increases with age. Despite both processes being associated with immune activation and inflammation, little is known about the mechanistic interactions between neurodegenerative disease and arthritis. In this article, we show that tau-transgenic (tau-tg) mice that develop neurodegenerative disease characterized by deposition of tau tangles in the brain are highly susceptible to developing arthritis. Already at steady-state conditions, tau-tg mice exhibit peripheral immune activation that is manifested by higher numbers of granulocytes, plasmablasts, and inflammatory Ly6C(hi) CCR2(+) monocytes, as well as increased levels of proinflammatory cytokines, such as TNF-? and IL-17. Upon induction of collagen-induced arthritis (CIA), tau-tg mice displayed an increased incidence and an earlier onset of CIA that was associated with a more pronounced inflammatory cytokine response. Furthermore, induction of CIA led to significantly elevated numbers of Iba-1-expressing cells in the brain, indicative of microglia activation, and the formation of anti-tau Abs in tau-tg mice. These changes were accompanied by the resolution of tau tangles and significantly decreased neurodegenerative pathology. In summary, these data show that neurodegenerative disease enhances the development of arthritis. In addition, arthritis, once induced, triggers innate immune responses in the brain, leading to resolution of neurodegenerative change
EVALuna2:13302

Nintedanib macrophage activation and ameliorates vascular and fibrotic manifestations in the Fra2 mouse model of systemic sclerosis - Huang, Jingang; Maier, Christiane; Zhang, Yun; Soare, Alina; Dees, Clara; Beyer, Christian; Harre, Ulrike; Chen, Chih-Wei; Distler, Oliver; Schett, Georg; Wollin, Lutz; Distler, Jörg (Annals of the Rheumatic Diseases, 2017)
Nintedanib is an inhibitor targeting platelet-derived growth factor receptor, fibroblast growth factor receptor and vascular endothelial growth factor receptor tyrosine kinases that has recently been approved for the treatment of idiopathic pulmonary fibrosis. The aim of this study was to analyse the effects of nintedanib in the fos-related antigen-2 (Fra2) mouse model of systemic sclerosis (SSc).The effects of nintedanib on pulmonary arterial hypertension with proliferation of pulmonary vascular smooth muscle cells (PVSMCs) and luminal occlusion, on microvascular disease with apoptosis of microvascular endothelial cells (MVECs) and on fibroblast activation with myofibroblast differentiation and accumulation of extracellular matrix were analysed. We also studied the effects of nintedanib on the levels of key mediators involved in the pathogenesis of SSc and on macrophage polarisation.Nintedanib inhibited proliferation of PVSMCs and prevented thickening of the vessel walls and luminal occlusion of pulmonary arteries. Treatment with nintedanib also inhibited apoptosis of MVECs and blunted the capillary rarefaction in Fra2-transgenic mice. These effects were associated with a normalisation of the serum levels of vascular endothelial growth factor in Fra2 mice on treatment with nintedanib. Nintedanib also effectively blocked myofibroblast differentiation and reduced pulmonary, dermal and myocardial fibrosis in Fra2-transgenic mice. The antifibrotic effects of nintedanib were associated with impaired M2 polarisation of monocytes and reduced numbers of M2 macrophages.Nintedanib targets core features of SSc in Fra2-transgenic mice and ameliorates histological features of pulmonary arterial hypertension, destructive microangiopathy and pulmonary and dermal fibrosis. These data might have direct implications for the ongoing phase III clinical trial with nintedanib in SSc-associated interstitial lung diseas
EVALuna2:13441

Novel Mechanism Mediated By the IL-23/Th17 Axis Contributing to Auto-Immune Arthritis - Pfeifle, René; Rothe, Tobias; Ipseiz, Natacha; Culemann, Stephan; Harre, Ulrike; Krönke, Gerhard; Schett, Georg (2016)
EVALuna2:35064

Novel mechanism mediated by the IL23/Th17 axis contributing to auto-immune arthritis - Pfeifle, R.; Rothe, T.; Ipseiz, N.; Culemann, S.; Harre, Ulrike; Schett, Georg; Krönke, Gerhard (2017)
EVALuna2:34159

Osteocyte necrosis triggers osteoclast-mediated bone loss through macrophage-inducible C-type lectin - Andreev, Darja; Liu, Mengdan; Weidner, Daniela; Kachler, Katerina; Faas, Maria; Grüneboom, Anika; Schlötzer-Schrehardt, Ursula; Munoz, Luis Enrique; Steffen, Ulrike; Grötsch, Bettina; Killy, Barbara; Krönke, Gerhard; et al. (Journal of Clinical Investigation, 2020)
Although the control of bone-resorbing osteoclasts through osteocyte-derived RANKL is well defined, little is known about the regulation of osteoclasts by osteocyte death. Indeed, several skeletal diseases, such as bone fracture, osteonecrosis, and inflammation are characterized by excessive osteocyte death. Herein we show that osteoclasts sense damageassociated molecular patterns (DAMPs) released by necrotic osteocytes via macrophage-inducible C-type lectin (Mincle), which induced their differentiation and triggered bone loss. Osteoclasts showed robust Mincle expression upon exposure to necrotic osteocytes in vitro and in vivo. RNA sequencing and metabolic analyses demonstrated that Mincle activation triggers osteoclastogenesis via ITAM-based calcium signaling pathways, skewing osteoclast metabolism toward oxidative phosphorylation. Deletion of Mincle in vivo effectively blocked the activation of osteoclasts after induction of osteocyte death, improved fracture repair, and attenuated inflammation-mediated bone loss. Furthermore, in patients with osteonecrosis, Mincle was highly expressed at skeletal sites of osteocyte death and correlated with strong osteoclastic activity. Taken together, these data point to what we believe is a novel DAMP-mediated process that allows osteoclast activation and bone loss in the context of osteocyte death.
CRIS-Team Scopus Importer:2020-10-16

Pasteurella multocida toxin- induced osteoclastogenesis requires mTOR activation - Kloos, Bianca; Chakraborty, Sushmita; Lindner, Sonja G.; Noack, Katrin; Harre, Ulrike; Schett, Georg; Kraemer, Oliver H.; Kubatzky, Katharina F. (Cell Communication and Signaling, 2015)
Background: Pasteurella multocida toxin (PMT) is a potent inducer of osteoclast formation. Pigs suffering from an infection with toxigenic Pasteurella multocida strains develop atrophic rhinitis characterised by a loss of turbinate bones and conchae. However, on the molecular level the process of bone loss remains largely uncharacterised. Results: Recently it was found that PMT activates the serine/threonine kinase mammalian target of rapamycin (mTOR) in fibroblasts. Using RAW264.7 macrophages, we investigated the role of the mTOR complex 1 (mTORC1) in PMT-mediated osteoclast formation. PMT induces the differentiation of RAW264.7 macrophages into multinucleated, tartrate resistant acid phosphatase (TRAP) positive osteoclasts that are capable to resorb bone. In the presence of the mTORC1 inhibitor rapamycin, PMT was significantly less able to induce the formation of TRAP-positive osteoclasts. Accordingly, the resulting resorption of bone was strongly reduced. A major target of mTOR is the 70 kDa ribosomal protein S6 kinase 1 (p70 S6K1). Activated p70 S6K1 decreases the expression of programmed cell death protein 4 (PDCD4), a negative transcriptional regulator of osteoclastogenesis, at the protein and gene level. Ultimately this results in the activation of c-Jun, a component of the activator protein 1 (AP-1) complex, which is a major transcription factor for the induction of osteoclast-specific genes. We now demonstrate that c-Jun and its downstream target, the osteoclast-specific bone degrading protease cathepsin K, are upregulated upon PMT treatment in an mTOR-dependent manner. Conclusions: Activation of mTOR signalling plays a central role in the formation of osteoclasts through the bacterial toxin PMT. On the molecular level, PMT-induced activation of mTOR leads to down regulation of PDCD4, a known repressor of AP-1 complex, culminating in the activation of c-Jun, an essential transcription factor for triggering osteoclastogenesis.

Pasteurella multocida Toxin Triggers RANKL-Independent Osteoclastogenesis - Chakraborty, Sushmita; Kloos, Bianca; Harre, Ulrike; Schett, Georg; Kubatzky, Katharina F. (Frontiers in Immunology, 2017)
Bone remodeling is a continuous process to retain the structural integrity and function of the skeleton. A tight coupling is maintained between osteoclast-mediated resorption of old or damaged bones and osteoblast-mediated formation of new bones for bone homeostasis. While osteoblasts differentiate from mesenchymal stem cells, osteoclasts are hematopoietic in origin and derived from myeloid precursor cells. Osteoclast differentiation is driven by two cytokines, cytokine receptor activator of NF-?B ligand (RANKL), and macrophage colony-stimulating factor. Imbalances in the activity of osteoblasts and osteoclasts result in the development of bone disorders. Bacterially caused porcine atrophic rhinitis is characterized by a loss of nasal ventral conche bones and a distortion of the snout. While Bordetella bronchiseptica strains cause mild and reversible symptoms, infection of pigs with toxigenic Pasteurella multocida strains causes a severe and irreversible decay. The responsible virulence factor Pasteurella multocida toxin (PMT) contains a deamidase activity in its catalytical domain that constitutively activates specific heterotrimeric G proteins to induce downstream signaling cascades. While osteoblasts are inhibited by the toxin, osteoclasts are activated, thus skewing bone remodeling toward excessive bone degradation. Still, the mechanism by which PMT interferes with bone homeostasis, and the reason for this unusual target tissue is not yet well understood. Here, we show that PMT has the potential to differentiate bone marrow-derived macrophages into functional osteoclasts. This toxin-mediated differentiation process is independent of RANKL, a cytokine believed to be indispensable for triggering osteoclastogenesis, as addition of osteoprotegerin to PMT-treated macrophages does not show any effect on PMT-induced osteoclast formation. Although RANKL is not a prerequisite, toxin-primed macrophages show enhanced responsiveness to low concentrations of RANKL, suggesting that the PMT-generated microenvironment offers conditions where low concentrations of RANKL lead to an increase in the number of osteoclasts resulting in increased resorption. PMT-mediated release of the osteoclastogenic cytokines such as IL-6 and TNF-?, but not IL-1, supports the differentiation process. Although the production of cytokines and the subsequent activation of signaling cascades are necessary for PMT-mediated differentiation into osteoclasts, they are not sufficient and PMT-induced activation of G protein signaling is essential for efficient osteoclastogenesi
EVALuna2:13413

Periarticular Bone Loss in Arthritis Is Induced By Autoantibodies Against Citrullinated Vimentin - Engdahl, Cecilia; Bang, Holger; Dietel, Katharina; Lang, Stefanie; Harre, Ulrike; Schett, Georg (2016)
EVALuna2:33224

Periarticular Bone Loss in Arthritis Is Induced by Autoantibodies Against Citrullinated Vimentin - Engdahl, Cecilia; Bang, Holger; Dietel, Katharina; Lang, Stefanie; Harre, Ulrike; Schett, Georg (Journal of Bone and Mineral Research, 2017)
Periarticular bone loss is a long known but yet insufficiently understood phenomenon in patients with rheumatoid arthritis. This study investigated whether autoimmunity against citrullinated proteins is causally involved in triggering periarticular bone loss. Periarticular bone loss was studied in the standard antigen-induced arthritis (AIA) mouse model with methylated bovine serum albumin (mBSA) as well as a modified model with mutated citrullinated vimentin (MCV) alone or in combination with mBSA. Periarticular bone loss, subchondral osteoclastogenesis, as well as local expression of cytokines, osteoclast genes, and peptidyl-arginine deiminase (PAD) enzymes were assessed after arthritis induction. Immune cell and osteoclast precursor infiltration were detected in the periarticular bone marrow and local lymph nodes. In addition, periarticular bone loss was assessed upon challenge of mice with purified anti-MCV antibody. Despite inducing a milder form of arthritis than mBSA, MCV triggered significant periarticular bone loss associated with an increased infiltration of osteoclast precursors and mature osteoclasts in the periarticular bone marrow. MCV enhanced the expression of the osteoclast inducers RANKL and M-CSF, the cytokines IL-8, IL-1, IL-6, and TNF-?, as well as PAD2 and PAD4 enzymes in the periarticular bone marrow. Furthermore, also anti-MCV antibody challenge induced significant periarticular bone loss and local osteoclastogenesis in the mice. Autoimmunity against citrullinated vimentin triggers periarticular bone loss by osteoclast activation in the bone marrow. These findings may explain why periarticular bone loss is already found very early in the disease course of patients with rheumatoid arthritis. © 2017 American Society for Bone and Mineral Research.
EVALuna2:13415

Regulation of autoantibody activity by the IL-23-TH17 axis determines the onset of autoimmune disease. - Pfeifle, René; Rothe, Tobias; Ipseiz, Natacha; Scherer, Hans U.; Culemann, Stephan; Harre, Ulrike; Ackermann, Jochen; Seefried, Martina; Kleyer, Arnd; Uderhardt, Stefan; Haugg, Benjamin; Huebert, Axel J.; et al. (Nature Immunology, 2017)
The checkpoints and mechanisms that contribute to autoantibody-driven disease are as yet incompletely understood. Here we identified the axis of interleukin 23 (IL-23) and the TH17 subset of helper T cells as a decisive factor that controlled the intrinsic inflammatory activity of autoantibodies and triggered the clinical onset of autoimmune arthritis. By instructing B cells in an IL-22- and IL-21-dependent manner, TH17 cells regulated the expression of β-galactoside α2,6-sialyltransferase 1 in newly differentiating antibody-producing cells and determined the glycosylation profile and activity of immunoglobulin G (IgG) produced by the plasma cells that subsequently emerged. Asymptomatic humans with rheumatoid arthritis (RA)-specific autoantibodies showed identical changes in the activity and glycosylation of autoreactive IgG antibodies before shifting to the inflammatory phase of RA; thus, our results identify an IL-23-TH17 cell-dependent pathway that controls autoantibody activity and unmasks a preexisting breach in immunotoleranc

Suppression of neutrophils by sodium exacerbates oxidative stress and arthritis - Zlatar, Leticija; Mahajan, Aparna; Munoz Becerra, Marco; Weidner, Daniela; Bila, Galyna; Bilyy, Rostyslav; Titze, Jens; Hoffmann, Markus H.; Schett, Georg; Herrmann, Martin; Steffen, Ulrike; Muñoz, Luis E.; et al. (Frontiers in Immunology, 2023)
Introduction: Typical Western diet, rich in salt, contributes to autoimmune disease development. However, conflicting reports exist about the effect of salt on neutrophil effector functions, also in the context of arthritis. Methods: We investigated the effect of sodium chloride (NaCl) on neutrophil viability and functions in vitro, and in vivo employing the murine K/BxN-serum transfer arthritis (STA) model. Results and discussion: The effects of NaCl and external reactive oxygen species (H2O2) were further examined on osteoclasts in vitro. Hypertonic sodium-rich media caused primary/secondary cell necrosis, altered the nuclear morphology, inhibited phagocytosis, degranulation, myeloperoxidase (MPO) peroxidation activity and neutrophil extracellular trap (NET) formation, while increasing total ROS production, mitochondrial ROS production, and neutrophil elastase (NE) activity. High salt diet (HSD) aggravated arthritis by increasing inflammation, bone erosion, and osteoclast differentiation, accompanied by increased NE expression and activity. Osteoclast differentiation was decreased with 25 mM NaCl or 100 nM H2O2 addition to isotonic media. In contrast to NaCl, external H2O2 had pro-resorptive effects in vitro. We postulate that in arthritis under HSD, increased bone erosion can be attributed to an enhanced oxidative milieu maintained by infiltrating neutrophils, rather than a direct effect of NaCl.
CRIS-Team Scopus Importer:2023-09-01
Keywords: K/BxN serum transfer arthritis; neutrophil extracellular traps (NETs); neutrophils; osteoclasts; reactive oxygen species; sodium chloride

T cells as key players for bone destruction in gouty arthritis? - Harre, Ulrike; Derer, Anja; Schorn, Christine; Schett, Georg; Herrmann, Martin (Arthritis Research & Therapy, 2011)
The deposition of monosodium urate (MSU) crystals in synovial fluid and tissue leads to gouty arthritis frequently associated with synovial inflammation and bone erosions. The cellular mechanism that links MSU crystals to an increased number of osteoclasts has not yet been fully understood. In a recent issue of Arthritis Research & Therapy Lee and colleagues proposed that bone destruction in chronic gouty arthritis is at least in part dependent on expression by T cells of receptor activator of NF-κB ligand (RANKL). The authors showed that pro-resorptive cytokines such as IL-1β, IL-6, and TNFα are expressed within tophi and stromal infiltrates. In vitro stimulation with MSU crystals revealed monocytes as a source for these cytokines, whereas T cells produce RANKL, the major trigger of osteoclastogenesis. © 2011 BioMed Central Ltd.
Created from Fastlane, Scopus look-up

The complement system drives local inflammatory tissue priming by metabolic reprogramming of synovial fibroblasts - Friščić, Jasna; Böttcher, Martin; Reinwald, Christiane; Bruns, Heiko; Wirth, Benjamin; Popp, Sebastian; Walker, Kellie Irene; Ackermann, Jochen A.; Chen, Xi; Turner, Jason; Zhu, Honglin; Seyler, Lisa; et al. (Immunity, 2021)
Arthritis typically involves recurrence and progressive worsening at specific predilection sites, but the checkpoints between remission and persistence remain unknown. Here, we defined the molecular and cellular mechanisms of this inflammation-mediated tissue priming. Re-exposure to inflammatory stimuli caused aggravated arthritis in rodent models. Tissue priming developed locally and independently of adaptive immunity. Repeatedly stimulated primed synovial fibroblasts (SFs) exhibited enhanced metabolic activity inducing functional changes with intensified migration, invasiveness and osteoclastogenesis. Meanwhile, human SF from patients with established arthritis displayed a similar primed phenotype. Transcriptomic and epigenomic analyses as well as genetic and pharmacological targeting demonstrated that inflammatory tissue priming relies on intracellular complement C3- and C3a receptor-activation and downstream mammalian target of rapamycin- and hypoxia-inducible factor 1α-mediated metabolic SF invigoration that prevents activation-induced senescence, enhances NLRP3 inflammasome activity, and in consequence sensitizes tissue for inflammation. Our study suggests possibilities for therapeutic intervention abrogating tissue priming without immunosuppression.
CRIS-Team Scopus Importer:2021-04-19
Keywords: arthritis; cell metabolism; cellular senescence; complement system; inflammasome; inflammation; mechanistic target of rapamycin; synovial fibroblasts; tissue priming; trained immunity

The human sialic acid-binding immunoglobulin-like lectin Siglec-9 and its murine homolog Siglec-E control osteoclast activity and bone resorption - Andes, F. T.; Adam, Susanne; Hahn, Madelaine; Aust, O.; Frey, Silke; Grüneboom, Anika; Nitschke, Lars; Schett, Georg; Steffen, Ulrike (Bone, 2020)
Regulation of osteoclast differentiation and function is a central element in bone homeostasis. While the role of soluble factors, such as cytokines, hormones and growth factors, in controlling osteoclast differentiation has been intensively characterized, the function of surface receptors is less well understood. Sialic acid-binding immunoglobulin-like lectin (Siglec)-9 and its murine homolog Siglec-E are sialic acid-recognizing inhibitory receptors from the CD33-related Siglec-family and mainly expressed on myeloid cells. We found Siglec-9 and Siglec-E to be expressed at all stages of human and murine osteoclastogenesis, respectively. Siglec-E knockout mice displayed lower bone mass despite unchanged osteoclast numbers and an increased bone formation rate. Ex vivo osteoclast assays using Siglec-E knockout cells or a blocking antibody against human Siglec-9 confirmed the suppressive effect of Siglec-9/Siglec-E on osteoclast function. Although osteoclast numbers were unchanged or even slightly decreased, the blockade/absence of Siglec-9/Siglec-E resulted in an augmented resorption activity of mature osteoclasts. This increased resorption activity was associated with enlarged actin rings. Together, our results suggest Siglec-9/Siglec-E to inhibit osteoclast activation independently from osteoclast differentiation and thereby propose a new mechanism for the control of local bone resorption.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Bone; Osteoclasts; Resorption; Siglec-9; Siglec-E

The Role of Autoantibodies in Bone Metabolism and Bone Loss - Hauser, Barbara; Harre, Ulrike (Calcified Tissue International, 2018)
Many autoimmune diseases are associated with deranged bone metabolism. The resulting localized or systemic bone loss can compromise the quality of life of patients by causing local bone deformities or fragility fractures. There is emerging evidence that antibodies have a direct impact on key players of bone homeostasis, in particular osteoclasts. Clinical and pre-clinical studies provide insight into the function of autoantibodies related to Rheumatoid Arthritis (rheumatoid factor, anti-citrullinated protein antibodies, and anti-carbamylated protein antibodies) and their inflammation-independent interaction with bone cells. Furthermore, we summarize the current knowledge about neutralizing antibodies to the antiresorptive protein osteoprotegerin, which have been described in patients with Coeliac Disease, Rheumatoid Arthritis, and Spondyloarthritis.
Created from Fastlane, Scopus look-up
Keywords: ACPA; Autoantibodies; Bone loss; Osteoclast; Osteoprotegerin; Rheumatoid arthritis

The Role of Dietary Fiber in Rheumatoid Arthritis Patients: A Feasibility Study - Häger, Julian; Bang, Holger; Hagen, Melanie; Frech, Michael; Träger, Pascal; Sokolova, Maria V.; Steffen, Ulrike; Tascilar, Koray; Sarter, Kerstin; Schett, Georg; Rech, Jürgen; Zaiss, Mario (Nutrients, 2019)
Short-chain fatty acids are microbial metabolites that have been shown to be key regulators of the gut-joint axis in animal models. In humans, microbial dysbiosis was observed in rheumatoid arthritis (RA) patients as well as in those at-risk to develop RA, and is thought to be an environmental trigger for the development of clinical disease. At the same time, diet has a proven impact on maintaining intestinal microbial homeostasis. Given this association, we performed a feasibility study in RA patients using high-fiber dietary supplementation with the objective to restore microbial homeostasis and promote the secretion of beneficial immunomodulatory microbial metabolites. RA patients (n = 36) under routine care received daily high-fiber bars or cereals for 28 days. Clinical assessments and laboratory analysis of immune parameters in blood and stool samples from RA patients were done before and after the high-fiber dietary supplementation. We observed an increase in circulating regulatory T cell numbers, favorable Th1/Th17 ratios, as well as decreased markers of bone erosion in RA patients after 28 days of dietary intervention. Furthermore, patient-related outcomes of RA improved. Based on these results, we conclude that controlled clinical studies of high-fiber dietary interventions could be a viable approach to supplement or complement current pharmacological treatment strategies.
CRIS-Team Scopus Importer:2019-10-18
Keywords: gut–joint axis; high-fiber diet (HFD); microbiota; rheumatoid arthritis (RA); short chain fatty acids (SCFA)

The ups and downs of bone in health and rheumatic disease - Harre, Ulrike; Schett, Georg (Nature Reviews Rheumatology, 2013)
Created from Fastlane, Scopus look-up